Eucharystia : znak ku życiu nienarodzonych - Dziuba, Andrzej (Ius Matrimoniale, 2001)
Our commitment to defend our pre -born brothers and sisters receives its form and sustenance from the Eucharist as a Sacrament of faith, unity, life, worship, and love. The Eucharist is a Sacrament of faith. The Consecrated Hoste looks no different after the consecration than before. It looks, smells, feels, and tastes like bread. Only one of the five senses gets to the truth. As St. Thomas' „Adoro Te Devote” expresses, „Seeing, touching, tasting are in Thee deceived. What says trusty hearing, that shall be believed?” The ears hear His words, „This is My Body; this is My Blood,” and faith takes us beyond the veil of appearances. The Eucharist is also a Sacrament of Unity. „When I am lifted up from the earth,” the Lord said, „I will draw all people to myself” (Jn. 12:32). He fulfills this promise in the Eucharist, which builds up the Church. The Church is the sign and cause of the unity of the human family. The Eucharist is the Sacrament of Life. „I am the Bread of Life. He who eats this bread will live forever. I will raise Him upon the last day.” (See Jn. 6:47-58). The Eucharistie sacrifice is the very action of Christ by which He destroyed our death and restored our life. Whenever we gather for this sacrifice we are celebrating the victory of life over death, and therefore over abortion. The pro-life movement is not simply working „for” victory; we are working „from” victory. The Eucharist is the Supreme act of Worship of God. Two lessons each person needs to learn are, „1. There is a God. 2. It isn't me.” The Eucharist, as the perfect sacrfice, acknowledges that God is God, and that „it is (His) right to receive the obedience of all creation” (Sacramentary, Preface for Weekdays III). The Eucharist is, finally, The Sacrament of Love. St. John explains, „This is how we know what love is: Jesus Christ laid down his life for us” (1 Jn. 3:16). Christ teaches, „Greater love than this no one has, than to lay down his life for his friends” ( Jn. 15:13). The best symbol of love is not the heart, but rather the crucifix. Abortion is the exact opposite of love. Love says, „I sacrifice myself for the good of the other person.” Abortion says, „I sacrifice the other person for the good of myself.” In the Eucharist we see the meaning of love and receive the power to live it. The very same words, further more, that the Lord uses to teach us the meaning of love are also used by those who promote abortion:„This is my body.” There four little words are spoken from opposite ends of the universe, with totally opposite results. Christ gives His body away so others might live; abortion supporters cling to their own bodies so others might die. Christ says „This is My Body given up for you; This is My Blood shed for you.” These are the words of sacrifice; these are the words of love. Everyone who wants to fight abortion needs to say the same. We need to exercise the same generosity we ask the mothers to exercise. We need to imitate the mysteries we celebrate. „Do this in memory of me ” applies to all of us in the sense that we are to lovingly suffer with Christ so others may live. We are to be like lightning rods in the midst of this terrible storm of violence and destruction, and say, „Yes, Lord, I am willing to absorb some of this violence and transform it by love into personal suffering, so that others may live.” Indeed, the Eucharist gives the pro-life movement its marching orders. It also provides the source of its energy, which is love. Indeed, if the pro-life movement is not a movement of love, then it is nothing at all. But if it is a movement of love, then nothing will stop it, for „Love is stronger than death, more powerful even than hell” (Song o f Songs 8:6).